Controlling Fibronectin Fibrillogenesis Using Visible Light - Gudzenko, Tetyana; Franz, Clemens M. (Frontiers in Molecular Biosciences, 2020)
We previously developed a surface-assisted assay to image early steps of cell-induced plasma fibronectin (FN) fibrillogenesis by timelapse atomic force microscopy (AFM). Unexpectedly, complementary attempts to visualize FN fibrillogenesis using fluorescently-labeled FN (Alexa Fluor 488 or 568) and live-cell light microscopy initially failed consistently. Further analysis revealed that fibrillar remodeling was inhibited efficiently in the focal area illuminated during fluorescence imaging, but progressed normally elsewhere on the substrate, suggesting photo sensitivity of the FN fibrillogenesis process. In agreement, active cell-driven fibrillar extension of FN could be stopped by transient illumination with visible light during AFM timelapse scanning. Phototoxic effects on the cells could be ruled out, because pre-illuminating the FN layer before cell seeding also blocked subsequent fibrillar formation. Varying the illumination wavelength range between 400 and 640 nm revealed strong inhibition across the visible spectrum up to 560 nm, and a decreasing inhibitory effect at longer wavelengths. The photo effect also affected unlabeled FN, but was enhanced by fluorophore labeling of FN. The inhibitory effect could be reduced when reactive oxygen species (ROS) were removed for the cell imaging medium. Based on these findings, FN fibrillogenesis could be imaged successfully using a labeling dye with a long excitation wavelength (Alexa Fluor 633, excitation at 632 nm) and ROS scavengers, such as oxyrase, in the imaging medium. Fibrillar remodeling of exposed cell-free FN layers by AFM scanning required higher scan forces compared to non-exposed FN, consisting with mechanical stiffing of the FN layer after illumination. In agreement with changes in FN mechanics, cells spreading on pre-exposed FN showed reduced migration speeds, altered focal adhesion arrangement, and changes in mechanosensitive signaling pathways, including reduced FAK (Y397) and paxillin (Y118) phosphorylation. Pre-exposure of FN to visible light prior to cell seeding thus provides a useful tool to delineate mechanosensitive signaling pathway related to FN fibrillogenesis. When using FN-coated cell adhesion substrates, care should be taken when comparing experimental results obtained on non-exposed FN layers in cell culture incubators, or during live-cell fluorescence imaging, as FN fibrillogenesis and mechanosensitive cellular signaling pathways may be affected differently.